Tecnologia móvel para consulta de enfermagem no atendimento às síndromes gripais e Covid-19 na atenção primária à saúde do Amazonas - Pimentão, Adriany da Rocha (2023)
Introduction: With the Covid-19 emergence and the challenges for contention and mitigation of the pandemic arose. In the Amazon scenario, due to the territorial extension, the care mediated by technologies emerges as a fast and effective solution for nursing care, especially in Primary Health Care. Objective: develop mobile technology for nursing consultation in the care of respiratory syndromes and Covid-19 in Primary Health Care in the Amazon. Method: This is a methodological study of innovative technological production, based on software engineering of mobile applications, developed in three stages. To define the prototype requirements and develop the screens, an integrative literature review was performed. Subsequently, data collection occurred in January 2023, utilizing a semi-structured form, intending to evaluate whether the developed screens were following the needs of the service. For the quantitative data analysis, descriptive statistics techniques were used, with the calculation of Cronbach's Alpha and the Content Validity Index. Results: 13 PHC nurses and 5 health technology specialists participated in the study. The mean age of the participants was 36±12.43 years, and the mean of their graduate time was 9±8.86 years. Also, at least 16 (83.33%) of the participants had some kind of graduate degree. After evaluating the prototype, they proposed adjustments to the mobile technology, which was evaluated according to three characteristics: the first related to the prototype's objectives, with a Cronbach's alpha of 0.86; the second related to its presentation and structuring, 0.94; and the third related to the relevance of the technological product, 0.55. Final considerations: The mobile technology prototype can support nurses in the diagnosis and treatment of people affected by influenza and Covid-19 syndromes during the nursing consultation, enhancing individualized, agile, and effective care, reducing the overload on the specialized network, and contributing to the advancement of best nursing practices in the context of Manaus. However, at this point, we understand the need to deepen the validation process of the technology to improve, especially, its relevance, an attribute in which a dissonance was identified between the quantitative assessment and the qualitative records of the participants.